Analysis of the alteration in the optical configuration of Raman spectrometer: Optimization of signal-to-noise ratio (SNR) in a specific wavelength range of clinical interest. Issue 6 (2008) - Lázaro Lázaro, João Carlos João Carlos; de Lima de Lima, Carlos J. Carlos J.; Moreira Moreira, Leonardo M. Leonardo M.; Silveira Jr. Silveira Jr., Landulfo Landulfo; da Silveira da Silveira, Nelson J. F. Nelson J. F.; Villaverde Villaverde, Antonio Balbin Antonio Balbin; Pacheco Pacheco, Marcos Tadeu T. Marcos Tadeu T.
Abstract : The present article is focused on the optimization of the optical parameters of a Raman spectrometer in order to obtain a minimum width of its spectral lines. In this way, using as reference the width of a fingerprint band of a calcified biological tissue, a spectral line without distortion or any loss of resolution was identified. This optimization is employed with the aim of improvement of the signal-to-noise ratio (SNR). A great improvement in the efficiency of the spectral collect was obtained, which can reduce significantly the time of diagnosis of target tissues, such as the calcified coronarian tissue. Therefore, the potential application of this new spectroscopic system increases the efficiency and precision, favoring the security of this technique to future in vivo applications. The excellent results obtained in this work become this spectroscopic system a powerful tool to the clinical diagnosis of several diseases.